Peculiar clinical and diagnostic features of infective endocarditis in Yemen: Comparative analysis with a Western University Hospital. (February 2023) - Al-Kebsi, Mohammed; Al-Motarreb, Ahmed; Al-Kadasi, Huda; Al-Muqayad, Mohammad Hussain; Mangieri, Enrico; Capotosto, Lidia; Miraldi, Fabio; Mastroianni, Claudio; Vitarelli, Antonio
The aim of this study was to describe the pattern, characteristics, and outcomes of infective endocarditis (IE) in Yemen and compare the results with the findings of a Western university hospital. Patients (pts) with a final diagnosis of IE observed in Al-Thawra Sanaa Cardiac Center were prospectively enrolled in 1-year time period. Clinical and diagnostic findings were compared to clinical and diagnostic data of 50 pts with IE observed at Sapienza University Hospital in Rome, Italy. The mean age was 38 ± 6. Predisposing factors for IE were rheumatic heart disease (RHD) in 34 pts (68%), congenital heart disease in 9 pts (18%), prosthetic valve IE in 4 pts (8%), and previous IE in 3 pts (6%). Transthoracic echocardiography (TTE) was done in 50 pts and transesophageal echocardiography (TEE) in 25. Blood cultures were taken in all pts and were positive in 3 pts (6%) and negative in 47 (94%). TTE was positive in 34/50 pts (68%) and TEE in 20/25 (80%). Compared to Sapienza University pts, Al-Thawra Cardiac Center pts had a younger age (p = 0.003), more predisposing RHD (p = 0.0004), less prosthetic heart valves IE (p = 0.002), and more negative blood cultures (p = 0.0001). IE is still a common disease in Yemen among RHD pts and affects the younger age group. It has severe complications which need early diagnosis and proper management. Echocardiography is of prime diagnostic value in the absence of positive blood cultures. An effort should be made to prevent rheumatic fever and RHD.